1998
DOI: 10.1055/s-0037-1615187
|View full text |Cite
|
Sign up to set email alerts
|

Factor Xa Cleavage of Tissue Factor Pathway Inhibitor Is Associated with Loss of Anticoagulant Activity

Abstract: SummaryTissue factor : factor VIIa induced activation of blood coagulation is inhibited by the complex between factor Xa and tissue factor pathway inhibitor (factor Xa : TFPI). We recently reported that phospholipid-bound factor Xa reduces the high binding affinity of factor Xa : TFPI for negatively charged phospholipids by a partial degradation of TFPI (17). The present study was undertaken to elucidate the factor Xa cleavage sites in TFPI and to delineate the consequences of this proteolysis with respect to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0
1

Year Published

1998
1998
2023
2023

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 39 publications
(46 reference statements)
1
21
0
1
Order By: Relevance
“…A previous study has shown that factor Xa can cleave the Lys86-Thr87 peptide bond between the K1 and K2 domains in recombinant TFPI. 33 Cleavage after Lys86 leads to the release of an N-terminal peptide with a calculated molecular mass of 10.08 kDa from mature TFPI, closely matching our observed size difference. This finding strongly suggests that the procoagulant effect of APC is mediated by cleavage of the TFPI Lys86-Thr87 peptide bond.…”
Section: Discussionsupporting
confidence: 81%
“…A previous study has shown that factor Xa can cleave the Lys86-Thr87 peptide bond between the K1 and K2 domains in recombinant TFPI. 33 Cleavage after Lys86 leads to the release of an N-terminal peptide with a calculated molecular mass of 10.08 kDa from mature TFPI, closely matching our observed size difference. This finding strongly suggests that the procoagulant effect of APC is mediated by cleavage of the TFPI Lys86-Thr87 peptide bond.…”
Section: Discussionsupporting
confidence: 81%
“…These include thrombin, plasmin, neutrophil elastase, and certain matrix metalloproteinases. 73,74 FXa, a natural target for TFPI, will also proteolyse TFPI after the K3 P1 residue (Arg199), but only when in molar excess. Although the cleavage of TFPI in vivo has not been well characterized, the plasmin-dependent reduction of both plasma and monocyte cell surface TFPI has been demonstrated in patients after thrombolytic therapy.…”
Section: Plasma Tfpimentioning
confidence: 99%
“…In addition to a full-length TFPI, it has been shown that truncated forms lacking most of their C-terminal domains are present in plasma and that they exhibit reduced affinity for vascular wall proteoglycans. In vitro experiments indicate that TFPI can be cleaved into partially degraded forms by various proteases, such as thrombin, 8 plasmin, 9 factor Xa, 10 and cell-derived matrix metalloproteinases, 11 as summarized in Figure 3. It remains to be established how the truncated forms of TFPI are generated in vivo by these proteases and by other proteases under physiological and pathological conditions.…”
Section: Functional Domains Of Tfpimentioning
confidence: 99%